Simulation of a three probe reflectometer system / Nor Wahidah Misran - Misran, Nor Wahidah
This technical paper presents the simulation of a three probe reflectometer system. Using software, it transforms the existence measurement system known as Reflectometer to Microstrip circuit. This involves design a circuit of Reflectometer using Genesys software. The simulation results and publish data from reflectometer measurement system will be compared. Thus, the output of this measurement can be used for obtaining the complex reflection coefficient of a material. The microstrip circuit will be fabricated and the Reflectometer measurement system will be smaller and portable.